Utilization of Pineapple Bromelain Enzymes (Ananas comosus) on Organoleptic, Physical and Chemical Quality of Mozzarella Cheese - Rahmawati, Nurina; Afiyah, Dyah Nurul; Alfianti, Putri (Universitas Halu Oleo, 2022)
This study aims to determine the effect of using pineapple bromelain enzymes with different levels on the organoleptic, physical and chemical quality of mozzarella cheese and to obtain the best levels of bromelain enzymes in the manufacture of mozzarella cheese. This research was conducted from July to October 2021 at the Animal Husbandry Laboratory, Faculty of Agriculture, Kadiri Islamic University. The method used is a completely randomized design (CRD). This study used 4 treatments and 5 replications, namely: T0 (100% pasteurized cow's milk + 1% rennet enzyme), T1 (100% pasteurized cow's milk + 1% bromelain enzyme), T2 (100% pasteurized cow's milk + 3% bromelain enzyme) and T3 (100% pasteurized cow's milk + 5% bromelain enzyme). The research variables included the organoleptic, physical and chemical quality of Mozzarella cheese. Data were analyzed using Microsoft Excel program, then statistical analysis was performed using Completely Randomized Design Experiment (CRD) and analysis of variance, followed by Duncan's Multiple Range Test (UJBD) if there were different results. The results showed that the use of the bromelain enzyme had a very significant effect (P<0.01) on color, aroma, texture, pH, melting power and moisture content of Mozzarella cheese and significantly (P<0.05) on taste, curd weight, yield and cheese weight. The conclusion is that the use of bromelain enzymes with a level of 1% is the best level, namely color, aroma, texture, curd weight, yield, cheese weight and moisture content of Mozzarella cheese.Keywords: bromelain enzyme, mozzarella cheese, organoleptic quality, physical and chemical